BIRD BIOPOTENTIAL AGAINST THE CORRECTION OF NON-SPECIFIC RESISTANCE AND SPECIFIC IMMUNOGENESIS - Semenov Vladimir Grigoryevich; Baimukanov Aidar Dastanbekouly; Ivanov Nikolay Grigoryevich; Tadzhieva Aigul Kadyrbaevna; Karynbayev Amanbay Kambarbekovich; Karibayeva Dilaram Keudenbayevna (Scientific Journal of Pedagogy and Economics, 2019)
For the first time in the conditions of commercial poultry production of the Chuvash Republic, a system for realizing the bioresource potential of productive traits of meat and egg-laying chicken of Lohmann Brown variety was introduced, which provides for the activation of nonspecific resistance and specific immunogenesis of the body with the immunotropic drug PV-1, developed by scientists of the Chuvash State Agricultural Academy. It is scientifically grounded and experimentally proved that feeding chickens of the 1st, 2nd and 3rd experimental groups with the drug PV-1 at doses of 0.05 ml/kg, 0.10 ml/kg and 0.15 ml/kg of live weight, respectively, once a day for 10 days with a 10-day break, with the repetition of cycles up to their 111-day age, stimulates the growth and development of young birds. On the 110th day of scientific and economic tests, the young birds of the experimental groups exceeded in the live weight of peers in the control group by 5.4%, 7.1% and 10.1% (P<0.01-0.001), respectively. The dynamics of changes in the absolute and average daily gain in live weight of tested young birds depended on the dose of the drug, and the maximum efficiency was established at a dose of 0.15 ml per 1 kg of live weight. It was found that the use of the PV-1 contributes to an increase in erythropoiesis, leukopoiesis and protein metabolism, as well as immunobiological indicators of the hematological profile of nonspecific resistance of the bird organism from 60 days of age (P<0.01-0.001). An increase in the number of red blood cells and the concentration of hemoglobin in the blood of tested birds on the background of immunocorrection show an improvement in their hematopoiesis, and an increase in the number of leukocytes indicates the activation of cellular protective factors of the body. The total protein content in the experimental groups enhanced due to an increase in the number of albumin and gamma globulins. The activation of nonspecific resistance of the bird organism against the use of the PV-1 immunostimulating drug was established according to the parameters of phagocytic activity of leukocytes, phagocytic index, lysozyme and bactericidal activity of blood serum. Immunization of birds with the use of the immunotropic drug PV-1 is accompanied by immunity stress: at Gumboro disease vaccination of chickens, the titers of specific antibodies increases by 53.3%, at Newcastle disease vaccination - by 50.0%, and at egg drop syndrome (EDS -76) vaccination - by 26.5 % If the egg production of the initial laying hen for 68 weeks of life in the control group was 196, then in the first experimental group it was 9.2% more, in the second experimental group - 9.7% more, in the third experimental group - 17.8% more. Based on the average laying hen, egg production in the experimental groups was higher than in the control: in the 1st experimental - by 4.1%, in the 2nd experimental - by 5.4% and in the 3rd experimental - by 11.8%. Laying hens of the control group reached 50% egg-laying at the age of 158 days, in the 1st and 2nd experimental groups - at 152 days of age, in the 3rd experimental group - at 155 days of age. The climax of the egg-laying capacity of the laying hens of the tested groups was at the 6th month of egg-laying: in the control group at 199 days of age, the 1st experimental group at 192 days of age, in the 2nd experimental group at the age of 200 days, and in the 3rd experimental group at 183 days of age. Against the background of the intensification of immunogenesis and nonspecific resistance of the body to the pressure of environmental and technological stress factors of habitat, the safety of the bird increases. The safety for 4 weeks of growth was 98.3% in the control group, 98.3% in the 1st experimental group, and 100% in the 2nd and 3rd experimental groups. A study of the meat productivity of birds raised with the use of the PV-1 revealed an increase in slaughter yield by 1.7 - 5.0%, the yield of edible parts increased by 62±3.20 - 155±3.40 g (P<0.001). To actualize productivity, to enhance non-specific resistance and ensure bird safety, we recommend using the PV-1 immunostimulating drug at a dose of 0.15 ml per 1 kg of live weight by feeding with fodder once a day for 10 days with a 10-day break. To increase immunity against Gumboro, Newcastle and SSN-76 diseases, we recommend using the PV-1 at a dose of 0.1-0.15 ml per 1 kg of live weight by feeding with fodder 10-12 days before immunization.